Um estudo enunciativo da palavra "assim" em textos publicitários - Calegari, Silvana Aparecida (2010)
This study emphasizes the relation between enunciation and grammar, through a semantic enunciate study of the word so in advertising texts. From the definitions found in the traditional and the normative grammars on, it is noticed a relation between both grammars about the word so and its use, through the observation about the effect of the sense built in advertising portuguese texts. Therefore, the main objective of this study is to find an explanation, having as theoretical reference the Enunciation s Theory , written by Émile Benveniste, who verified that the study of the language depends of a double syntax: the language syntax and the enunciation syntax; a language as a sign system and language as intersubjective communication (language speech). It is found out that the double consideration of the sense depends of an intermediate unit between the language and the language speech (sign word). In order to study the sense of the word so, it is necessary a corpus of advertising texts taken from magazines like Nova Escola, Isto é and Veja from 2008/2009, in which it was noticed the presence of the word so. After seven enunciation analyses of the word, it was constituted the sense relation in each enunciation, through the syntax enunciation